Cardiac Effects of Thyrotropin Oversuppression with Levothyroxine in Young Women with Differentiated Thyroid Cancer - Kyung-Soon Hong; Jung-Woo Son; Ohk Hyun Ryu; Moon-Gi Choi; Ji Yeon Hong; Seong Jin Lee (International Journal of Endocrinology)
Background. We investigated the cardiac effects of TSH (thyroid-stimulating hormone) oversuppression in women with thyroidectomized differentiated thyroid cancer (DTC) during levothyroxine suppression therapy. Methods. Fourteen young female patients with DTC were enrolled. The duration of TSH-suppressive therapy was 5 to 9 years. They satisfied the following criteria: (1) a serum level of TSH < 0.1 mU/L in the intermediate-risk or TSH < 0.3 mU/L in the low-recurrence-risk group and (2) having been receiving a fixed dose of LT4 before the study. Controls matched for age, sex, and body mass index (BMI) were compared in terms of the levels of serum free T4, free T3, TSH, plasma N-terminal pro-brain natriuretic peptide (NT-pro-BNP), and cardiac functions and structures. Results. DTC patients and control subjects were well matched in heart rate and blood pressure. There were marked differences in serum TSH (P=0.001) and free T4 (P=0.002). However, there were no differences between the groups in serum free T3 and plasma NT-pro-BNP. Furthermore, there were nonsignificant differences in cardiac functions and structures between the groups. Conclusions. This study shows that TSH suppression therapy in women with DTC may be safe with respect to cardiac functions and structures despite intermittent oversuppression of TSH during long-term suppressive therapy. Trial Registration. This trial is registered with clinicaltrials.gov identifier NCT02645786.